Marvels of Ground Water Sharing - A Case Study of Farmers of Kummaravandlapally Village in Anathapur District of Andhra Pradesh - Rani, B. Renuka; Bhagyalakshmi; Reddy, Bakka (Journal of Agricultural Extension Management, 2020)
Groundwater is the preferred source of irrigation for many smallholder farmers on its involves its low capital cost. The depletion and contamination of groundwater require the development of a robust framework for utilization of groundwater and management practices for sharing ground water by communities. The present case study explains the success story of kummaravandlapally- a drought prone village in Anathapur district of Andhra Pradesh in a project initiated by Watershed Support Services and Activities Network (WASSAN) which aimed to increase producivity crops by providing protective irrigation and promote sharing of ground water by farmers. This study shows that the farmers increased their profit managining by sharing ground water, shifted to less water intensive crops and became model for other farmers in the area